A “third way” in the philippines: Voluntary organizing for a new disaster management paradigm - Brower, Ralph S. (Animo Repository, 2011)
This study illuminates the role of civil society actors in advocating for and helping implement The Philippine Disaster Risk Reduction and Management Act of 2010. We illustrate how these actors served as both bottom-up and top-down brokers and translators in communicating ideas and action between vulnerable communities they represent and policy actors in the Philippine national government. We situate their actions within the Philippines’ unique historical, cultural, political, and socio-economic context, noting the significance of their policy entrepreneurship by comparison to conditions a mere 25 years earlier, when the Marcos Regime would have hunted down and killed them for their activism. We conclude with observations about important contributions that the disaster risk reduction paradigm makes to development theory, and assert the importance of political and social goals, that are often drowned out by the dominant role that economics and ownership models hold in some Western conceptions of voluntary organizing. © 2011, Taylor & Francis Group, LLC. All rights reserved.